Revision of Vilargus Theron (Hemiptera: Cicadellidae: Deltocephalinae) from South Africa - Stiller, M. (Zootaxa, 2010)
The South African grass-feeding leafhopper Vilargus Theron is revised. Vilargus pumilicans (Naudé) is redescribed and the specific status of V. campanus (Naudé) is discussed. Seven new species of Vilargus are described: V. bicornicans sp. n., V. budenticans sp. n., V. dentulicans sp. n., V. lobulicans sp. n., V. simulans sp. n., V. triquetricans sp. n. and V. trunculicans sp. n. A key is provided to males and known females of Vilargus. The species of this genus are small, light brown leafhoppers, commonly associated with grass in the Grassland Biome of South Africa, and rarely from the Savanna and Fynbos Biomes.